1580 Lumbar Puncture(LP) In Infants and Children with Suspected Meningitis-Diagnostic Yield over 15 Years. (October 2012) - Barsoum, Z
Abstract : Background: Bacterial meningitis is a serious disease that leads to much anxiety among the medical profession and parents.LP has long been a key tool for the diagnosis of meningitis. Objectives: To determine the diagnostic yield from LP over 15 years in Mid Western region of Ireland. Methods: A retrospective cohort analysis of laboratory data of all lumbar punctures performed from July 1996 to December 2010 in Paediatric department Mid Western Regional Hospital and maternity Hospital-Limerick-Ireland. Results: 1487 LPs were performed from July 1996 to December 2010.646 samples were obtained from July 1996 to December 2000 and 463 samples obtained from January 2001 to December 2005. 378 LPs were performed from 2006 to 2010.967 patients (65%) were 2 years or younger.18/1487(1.2%) patients had bacterial meningitis from 2001 to 2010, 15/18 (83%) were infants. CSF leucocytosis was noted in 17/18 patients(94%). Nisseria meningitidis B and Strypt. Pneumoniae were isolated in 38% &27% of cases respectively. Serum PCR was positive in 77% of cases. CSF PCR was positive in 100% of cases. Both CSF and blood culture were positive in 44% of cases. Conclusion: The incidence of bacterial meningitis is decreasing due to effective vaccination(18/1487 patients (1.2%), 83% infants. The role of LP in the diagnosis of meningitis is crucial. Nisseria meningitidis type B is the leading cause of bacterial meningitis over the last decade. CSF leucocytes are better indicators of disease than white blood cells.CSF PCR testing is more sensitive than serum PCR in the diagnosis of disease and should be requested in all cases with suspected meningitis.